Penguatan Branding Aceh Tengah Melalui Sport Tourism Arung Jeram: Studi Kelayakan Dan Perumusan Strategi Promosi Destinasi Berbasis Komunitas - Dedi Saputra; Masyitah; Rahmad Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the potential of whitewater rafting as a sport tourism activity in Central Aceh and to formulate a community-based promotional strategy to strengthen destination branding. The research employed a descriptive qualitative approach, supported by quantitative data. Primary data were collected through field observations on the Peusangan and Wih Ni Reje Rivers, as well as interviews with tourism officials, rafting communities, business owners, and community leaders. Secondary data were obtained from regional planning documents, tourism statistics, and scientific literature. The analysis was conducted through a feasibility study (market, technical, socio-cultural, environmental, and economic), a SWOT analysis, and promotional strategies, utilizing the STP framework and the 7P Marketing Mix. The results show that Central Aceh has great potential as a sports tourism destination, with the main strengths being the beautiful landscape of the Gayo Highlands, the challenging character of the river, and the unique local culture. Tourism feasibility is demonstrated by the high interest of the younger generation, the safe river route for beginners, the openness of the Gayo community to tourism, the relatively well-maintained environmental conditions, and the opportunities for local economic growth. In conclusion, the development of whitewater rafting in Central Aceh has great potential to become a leading sports tourism destination, leveraging its natural beauty and local culture, if managed sustainably, with community involvement, and supported by effective promotional strategies. Keywords: Branding; Central Aceh; Sport Tourism; Whitewater Rafting; Destination Promotion